ANALISIS PERBANDINGAN LIKUIDITAS SAHAM RETURN SAHAM DAN HARGA SAHAM SEBELUM DAN SESUDAH PENGUMUMAN PEMECAHAN SAHAM (STOCK SPLIT) (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI 2016-2019) - Erwin Febriansyah; Fraternesi Fraternesi; Muhammad Rifaldi Ebta Deta (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2021)
The purpose of establishing a company is to seek maximum profit, one way to get investors is through the capital market. Because capital market investment is full of uncertainty or uncertain risk, investors need sufficient information in choosing a portfolio of shares to buy. One of the information that can be obtained by investors is the announcement of a stock split.The research objective was to determine the magnitude of the effect of stock splitting, in which the variables examined were trading liquidity, stock return and stock price. The data used in this study were conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) using 2016-2019 data. Total population as many as 77 companies, and a sample of 22 manufacturing companies. The sample selection technique used purposive sampling technique to collect data. The data analysis technique used was the pairwise difference test (T-test), using SPSS 21.0 software.With the data analysis technique using the paired difference test (T-test), the results of this study can be concluded before and after the stock split, there is a significant difference to the Trading Liquidity Variable sig 0.016, Stock Return sig 0.007, and Stock Price sig 0.000.Â Keywords: Stock split, Liquidity, Stock Return, Stock Price.